Immunohistochemical study of basement membrane collagen IV in uterine cervix carcinoma - Pinto, Glauce Aparecida; Vassallo, José; Andrade, Liliana Aparecida Lucci De Angelo; Magna, Luís Alberto (São Paulo Medical Journal, 1998)
CONTEXT: The integrity of basement membrane (BM) is damaged during the evolution of a benign or potentially malignant lesion into a malignant one, in which it may undergo several degrees of discontinuity as a necessary condition for the invasive process. Immunostaining for collagen IV, which is exclusively found in BM, has been used to evaluate its formation in neoplastic and benign lesions of several organs. OBJECTIVE: To investigate BM continuity pattern in squamous carcinoma "in situ" (CIS), microinvasive (MIC) and invasive (IC) squamous cell carcinoma of the uterine cervix, and to find out if BM expression could be useful in the diagnosis of early stromal invasion (MIC). DESIGN: Archival material between 1988 and 1993 was studied at the Pathological Anatomy Department - Unicamp. PROCEDURES: The selected cases, previously formalin fixed and paraffin embedded, were reviewed retrospectively by submitting them to immunohistochemical study via the avidin-biotin-peroxidase method using a monoclonal antibody anticollagen IV. RESULTS: In all, 17 cases of CIS, 16 of MIC and 21 of IC were evaluated. All IC cases showed evident BM discontinuity, either focal or diffuse. In the CIS group, a continuous BM pattern was predominant, being focally disrupted in only 2/17 cases (11.8%). The MIC group showed an intermediate pattern, but with a clear tendency to BM discontinuity in 10/16 cases (62.5%). Inflammatory infiltrate, a variable also studied, cannot be considered responsible for BM discontinuity, since there was no statistical correlation between them. CONCLUSION: We conclude that immunostaining for collagen IV may contribute to the diagnosis of stromal invasion by BM discontinuity.